Alkali-aggregate reaction in concrete roads and bridges - West, Graham (Thomas Telford, 1996)
The word 'concrete' stands in common usage for something that is solid and enduring. This is testimony to the belief in the performance of concrete as a construction material. It was therefore a shock when it became apparent that concrete could suffer from a form of internal disintegration, dubbed 'concrete cancer'. caused by the chemical reaction between alkalis in cement and the minerals in the aggregate. This book provides a sound understanding of the alkali-aggregate reaction and how it affects the design, construction and maintenance of concrete roads and bridges.